First report of Raoultella ornithinolytica carrying blaKPC-2 isolated from a dipteran muscoid collected in a garbage from a public hospital in Rio de Janeiro, Brazil - Carramaschi, Isabel Nogueira (2019)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Entomologia Médica e Forense. Rio de Janeiro, RJ, Brasil.